Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1139/m95-122
|View full text |Cite
|
Sign up to set email alerts
|

Electron spectroscopic imaging of encapsidated DNA in vaccinia virus

Abstract: We have used electron spectroscopic imaging to locate the phosphorus in vaccinia DNA in situ in unstained, ultrathin sections of virions. The phosphorus of the DNA backbone appeared to form a halo on the core periphery surrounding a phosphorus-impoverished central element. These results constrain models for how DNA could be packaged into mature vaccinia particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…First, our ultrastructural localization of the F18 protein within mature virions places it in a ring that surrounds the central, lucent core; in fact, the pattern of F18 localization within mature virions is quite similar to that seen for the A14 protein. Second, electron spectroscopic imaging of encapsidated DNA has also suggested that the genome may be localized in a ring that surrounds the central, lucent core of the virion (21). Taken together, these data suggest that the nucleoprotein complex may associate with proteins located on the inner face the viral membrane.…”
Section: Discussionmentioning
confidence: 91%
“…First, our ultrastructural localization of the F18 protein within mature virions places it in a ring that surrounds the central, lucent core; in fact, the pattern of F18 localization within mature virions is quite similar to that seen for the A14 protein. Second, electron spectroscopic imaging of encapsidated DNA has also suggested that the genome may be localized in a ring that surrounds the central, lucent core of the virion (21). Taken together, these data suggest that the nucleoprotein complex may associate with proteins located on the inner face the viral membrane.…”
Section: Discussionmentioning
confidence: 91%
“…Energy-filtered images were recorded and elemental maps constructed, either by the three energy window method [17,22] (with two images recorded below and one image recorded above the ionization edge energy), or with the jump ratio method [19,23] (just using one image recorded at energies below, and one image recorded above the edge energy of interest).…”
Section: Energy-filtered Transmission Electron Microscopymentioning
confidence: 99%
“…For EFTEM, it is thus most important to make the samples as thin as possible and omit additions of any heavy elements during the preparation. EFTEM has previously been used to study viral morphogenesis in infected cells [13,[17][18][19] but has to our knowledge never been applied in the study of viral structures without extensive preparations for imaging including embedding, staining, and sectioning.…”
Section: Introductionmentioning
confidence: 99%
“…The localization of chemically defined components in ultrathin sections of biological material has been a central subject of interest in structural biology for many years. In particular, the role of phosphorus as a position marker of nucleic acids is a topic that has deserved considerable effort (Ottensmeyer and Andrew, 1980;Bazett-Jones and Ottensmeyer, 1981;Adamson-Sharpe and Ottensmeyer, 1981;Korn et al, 1983;Ottensmeyer, 1984: Ottensmeyer et al, 1988;Rattner and Bazett-Jones, 1989;Heng et al, 1990;Ozel et al, 1990;Bazett-Jones, 1993: Harauz et al, 1995Abolhassani-Dadras et al, 1994, 1996Olins et al, 1996;Vazquez-Nin et al, 1996;Beniac et al, 1997a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Electron spectroscopic imaging of sectioned viruses has provided high-contrast imaging and an improvement of the resolution of the viral particles, also allowing a better detectability of the immunolabeling markers (Ozel et al, 1990). Also, P-maps were obtained using a two-window method to study the organization of encapsidated DNA in vaccinia virus (Harauz et al, 1995). Interpretation problems arose in this case due to the fact that the samples were conventionally fixed and embedded.…”
Section: Introductionmentioning
confidence: 99%